The philosopher in the kitchen: the role of mathematical modelling in explaining drumlin formation - Fowler, A (Taylor and Francis, 2018)
Scientific progress does not take place in a linear fashion, but often occurs through sudden advances following years of stagnation, in the course of which quite heated battles between proponents of different viewpoints can occur. In this paper, we review several instances of such debates, and use them to throw light on a current philosophical tussle between proponents of different explanations for the formation of drumlins, and other subglacial bedforms. We conclude that the differences of opinion which emerge in the literature may be more an issue of semantics rather than a fundamental disagreement about process. In addition, we provide a critical review of some recent theories of drumlin formation, highlighting their merits and demerits, as well as defending them against some of the criticism they have received.